IMPACT OF THE SIMBA KUAT PROGRAM (RAMBA SYNERGY IN THE FIELD OF SUPPORTING CLEAN AND HEALTHY LEISURE) ON HANDLING STUNTING - Setiawan, Hanif; Putra, Erwin Hendra; Hendrawan, Wawan; Aprilia, Eka; Rosadi, Hengky; Sari, Dewi Ratna (Ridwan Institute, 2024)
This paper seeks to analyze the impact of the Strong Synergy Program to Support Clean and Healthy Villages through the concept of